2019
DOI: 10.18203/2320-6012.ijrms20194999
|View full text |Cite
|
Sign up to set email alerts
|

An observational study on musculoskeletal manifestations in type 2 Diabetes mellitus in rural population of Himachal Pradesh, India

Abstract: Background: The prevalence of diabetes mellitus (DM) is increasing at an alarming rate throughout world. Diabetes is mostly known for vascular and neurological complications. Musculoskeletal manifestations though not as serious as neurovascular complications can be very disabling. These may involve, the upper as well as the lower limb. This study was performed with am to find out the prevalence of musculoskeletal manifestations in type 2 diabetics in a far-flung district of Himachal Pradesh, India.Methods: Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The length of the diabetes disease and musculoskeletal (MSK) symptoms were shown to be significantly correlated in 2019, with individuals who had the condition for longer than 10 years being more likely to experience these manifestations [23] . Insignificant association between the outcomes and the length of diabetes was found in contrast to Abate et al (14) the inability to pinpoint the age of diabetes development may be the cause of the lack of connection.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the diabetes disease and musculoskeletal (MSK) symptoms were shown to be significantly correlated in 2019, with individuals who had the condition for longer than 10 years being more likely to experience these manifestations [23] . Insignificant association between the outcomes and the length of diabetes was found in contrast to Abate et al (14) the inability to pinpoint the age of diabetes development may be the cause of the lack of connection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In 2019, a study done by Bhat TA et al . [ 3 ] concluded that there was a significant correlation between the duration of the diabetic disease and musculoskeletal (MSK) manifestations. They also observed that patients having diabetes for more than 10 years were more likely to develop these manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that who had DM for more than 10 years weremore likely to develop these manifestations. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%